Desenvolvimento de método de quantificação dos constituintes fenólicos e ação anti-radical de vinhos tintos nacionais e importados - Nascimento, Roberto Jefferson Bezerra do (2010)
Resveratrol (cis and trans) and quercetin are important components in ensuring the quality of wine because of the diversity of biological activities that they have. Studies quantifying these constituents in Brazilian wines are rarely reported in the literature, especially in wines from the Vale Submédio do São Francisco. The objectives of this work were to develop and validate a quantification method for cis-resveratrol, trans-resveratrol, total resveratrol and quercetin by HPLC-UV in red wines, to evaluate and correlate the levels of total phenolics by Folin-Ciocalteu method with the anti-radical activity determined usingm the DPPH radical method and to determine the potential for classification of wines from their chromatographic profiles. In the study 45 samples of red wines were analysed. From these, 30 samples were from Brazilian wines:15 of the Vale Submédio do São Francisco, 11 of Serra Gaucha and 4 of Campanha Gaucha. There were 15 samples of imported wines: 5 from Argentina, 5 from Chile and 5 from French. The method developed for quantification of resveratrol (cis and trans) and quercetin was validated andused in the quantification. The results showed that Brazilian wines have about nine times more cis-resveratrol than trans-resveratrol and this relationship is even more pronounced in the Vale do São Francisco, with about 17 times more cis-resveratrol than trans-resveratrol in red wines from this region. The French wines presented quercetin in an amount above the rest of the wine samples. It was also observed that the wines from the Vale do São Francisco had higher levels of total resveratrol, significantly higher than imported wines, with p=0.0381. The total phenolics content was markedly higher in the wines from the Vale do São Francisco in relation to wines from the South, with p=0.001. The study of anti-radical activity against the DPPH radical showed that all wines are active, with EC50<130 μg/mL. In the study of the chromatographic profiles of the wines four distinct groupings among the wines were found, with 87% of the samples from the Vale do São Francisco, 80% of Chileans wines, 60% of the Serra Gaucha wines and 55% of French wines. Taken toghether the results show that Brazilian wines presented high level of phenolics, especially the wines from Vale do Submédio do São Francisco. This is translated into high levels of bioactive substances such as resveratrol (cis and trans) and quercetin, as well the high antioxidant activity. The high intensity of solar light in Brazil, mainly in the Vale do São Francisco, may have been the main factor contributing to the high content of these constituents, thus contributing to the high degree of grouping shown by the wines of this region using multivariate analysis.